TAHFIZ ALQURAN DALAM KURIKULUM PESANTREN DARUL HUFFAZ AL-ARIF DAN PONDOK PESANTREN DARUL QURAN JENDERAL BESAR DR. ABDUL HARIS NASUTION - Rangkuti, Fatima Rahma (Islamijah: Journal of Islamic Social Sciences, 2023)
This research is to analyze Tahfiz Alquran in the curriculum of Darul Huffaz Al-Arif Islamic Boarding School and Darul Quran Islamic Boarding School General Dr. Abdul Haris Nasution with qualitative research methods. The research data sources are: primary data sources and secondary data sources using data collection tools or instruments consisting of observation, unstructured interviews and documentation. The research findings are that Darul Huffaz Al-Arif Islamic Boarding School makes Tahfiz Quran lessons as the only main / compulsory subject in its curriculum, while Tahfiz Quran in the curriculum of Darul Quran Islamic Boarding School General Besar Dr. Abdul Haris Nasution, Tahfiz Quran is a compulsory subject for all students, coupled with the National curriculum for students who attend MTs / MA education in pesantren.